Brassinosteroids and Response of Plants to Heavy Metals Action - Rajewska, Iwona; Talarek, Marta; Bajguz, Andrzej (Frontiers in Plant Science, 2016)
Brassinosteroids (BRs) are a widespread group of plant hormones. These phytohormones play a crucial role in the regulation of growth and development of various plant species, and they demonstrate high biological activity. BRs are considered to demonstrate protective activity in the plants exposed to various stresses. Due to rapid industrialization and urbanization, heavy metals have become one of the most important plant stressors. In plants, accumulation of heavy metals beyond the critical levels leads to oxidative stress. However, BRs may inhibit the degradation of lipids, resulted from the overproduction of reactive oxygen species under stress conditions, and increase the activity of antioxidants. They also have the ability to promote phytochelatins synthesis.